2008
DOI: 10.1149/1.2990719
|View full text |Cite
|
Sign up to set email alerts
|

Au–ZnO and Pt–ZnO Films Prepared by Electrodeposition as Photocatalysts

Abstract: Metal–semiconductor Au–ZnO and Pt–ZnO films were prepared for enhancing ZnO photocatalytic activity. To increase the photocatalytic area in a metal–semiconductor material system, we introduce an efficient method where the metal and semiconductor are codeposited by an electrochemical method. The photocatalytic activity of Au–ZnO shows a better performance than that of Pt–ZnO determined by the degradation ability of methelene blue. There is an optimized Au concentration (∼2%) in Au–ZnO film for its best photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Being a wide and direct band gap ($3.37 eV) material with a large exciton binding energy (60 meV) and efficient light emission, semiconducting ZnO is a promising candidate for opto-electronics, 12,13 solar-cells, 14 sensors, 15 catalysis 16,17 and biological 18 applications. [22][23][24] Hybrid nanostructures consisting of Au and ZnO (ZnO:Au nanocomposites) with novel properties can be tailored for use in applications such as photo-catalysis, 25 biosensors 26 and solar cells. Noble metal NPs such as Ag and Au possess strong optical absorption at $430 nm and $530 nm by their plasmon resonances, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Being a wide and direct band gap ($3.37 eV) material with a large exciton binding energy (60 meV) and efficient light emission, semiconducting ZnO is a promising candidate for opto-electronics, 12,13 solar-cells, 14 sensors, 15 catalysis 16,17 and biological 18 applications. [22][23][24] Hybrid nanostructures consisting of Au and ZnO (ZnO:Au nanocomposites) with novel properties can be tailored for use in applications such as photo-catalysis, 25 biosensors 26 and solar cells. Noble metal NPs such as Ag and Au possess strong optical absorption at $430 nm and $530 nm by their plasmon resonances, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions are generally carried out to degrade the toxic and hazardous effluents left out in the eco system by chemical industries. In spite of the rich meritorious traits available in ZnO, the lack of their ability to absorb visible portion of solar radiation has been reported to hinder their photocatalytic activity significantly [9,10]. Likewise, the higher recombination rate of electron-hole pairs in ZnO (on irradiation) has also been reported to suppress their efficiency considerably (as these reactions takes place at the interface between catalyst and pollutant).…”
Section: Introductionmentioning
confidence: 99%
“…Under irradiation, the electrons promoted from VB to CB of semiconductor will be captured by the metal NPs, prohibiting the recombination of photo-generated carriers and thus improving the photoelectrochemical performance of the semiconductor particles [22]. It was demonstrated that Pt/ZnO and Au/ZnO exhibited enhanced photocatalytic activity [23][24][25][26][27][28][29]. However, the high price of Pt and Au is a concern for widespread industrial use.…”
Section: Introductionmentioning
confidence: 99%